Comparative analysis of the probability in digital wireless communication systems - Zhelev, Stefan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Digital signals dominate satellite communications systems. A measure the quality of digital signals is Bit Error Rate (BER) and Symbol Error Rate (SER). The main purpose of the paper is a comparison of the probability of error for various modulation and demodulation schemes used in digital communications systems (DCS) for transmitting information over channel. Error Rate parameters are resulting analytically, not experimentally.